Ionospheric total electron content disturbance associated with May 12, 2008, Wenchuan earthquake - Li, Jianyong; Meng, Guojie; You, Xinzhao; Zhang, Rui; Shi, Hongbo; Han, Yufei (Geodesy and Geodynamics, 2015)
Possible ionospheric disturbances relating to the May 12, 2008, MsS.0 Wenchuan earthquake were identified by Global Positioning System （GPS）-derived total electron content （TEC）, ion- osonde observations, the global ionospheric map （GIM）, and electron density profiles detected by the Constellation Observation System for Meteorology Ionosphere and Climate （COSMIC）. We applied a statistical test to detect anomalous TEC signals and found that a unique enhancement in TEC, recorded at 16 GPS stations, appeared on May 9, 2008. The critical fre- quency at F2 peak （foF2）, observed by the Chinese ionosondes, and maximal plasma frequency, derived from COSMIC data, revealed a characteristic similar to GPS TEC variations. The GIM showed that the anomalous variations of May 9 were located southeast of the epicenter. Using GPS data from 13 stations near the epicenter, we analyzed the TEC variations of satellite orbit traces during 04：00-11：00 UT. We found that TEC decreased to the east and increased to the southeast of the epicenter during this period. Results showed that the abnormal disturbance on May 9 was probably an ionosphenc precursor of the Wenchuan earthquake of May 12, 2008.